HARMONISASI ANTAR UMAT BERAGAMA DI LOMBOK - Wirata, I Wayan (PANGKAJA: JURNAL AGAMA HINDU, 2018)
Cultural diversity in the middle of pluralism is one of the assets of national and state life in Indone- sia. Culture, then, is thus one of the most appropriate alternatives for integrating ethnicity, ethnicity and religion under an inclusive and democratic order. With the appreciation of culture and the pres- ervation of traditional valuesÂ  w ill create a harmony and integrity of Lombok society. In some Hindu literature the concept of unity and unity is contained in the teaching of kuntumbakam and tatvam ation which means all brothers and I are you. Thus the unity, brotherhood, and togetherness creates a family atmosphere towards peace. The existence of such understanding and views as a strong foundation so as to stimulate the presence of caring and and togetherness that is based on a sense of affection towards others. It is necessary to get serious attention in order to cultivate increasing the harmony and adherence of religious people in Lombok. Referring to the above view there are several things that can be used as a reference in increasing harmonization of religious harmony in Hinduâ€™s view: a) Eliminating feelings of suspicion or hostility towards followers of other religions; b) Does not marginalize or blame a person for making a mistake; c) Providing a sense of appreciation of other people in carrying out their worship, in addition to not interfere with other people who are worshiping; and d) avoid discrimination against other religions.